ISCHEMIC HEART DISEASE AND SPECIFICS OF PERIPHERAL MICROCIRCULATION IN VARIOUS AGE GROUPS - O. V. Kamenskaya; A. M. Karas'kov; A. M. Chernyavsky; A. S. Klinkova (Российский кардиологический журнал, 2014)
Aim. To assess the condition of peripheral microcirculatory circulation (MCC) in patients with coronary heart disease (CHD) depending on the age, before and after revasculatization during different stages of operation treatment. Material and methods. Totally 40 patients with CHD included. Two groups completed: 1-24 patients with the age up to 60 and 2-16 patients older than 60. The condition of MCC in lower limbs studied by laser-doppler flowmetry (LDF) using the occlusion test, before revascularization and level of peripheral MCC at different stages of surgical intervention.Results. In those older than 60 we found lower level of MCC and lowered reactivity of microcirculatory bed. Lowering of the capillary reserve (CR) was found in two patients of both groups. The lowest level of peripheral MCC in both groups was detected at 30th min. of artificial circulation; at the end of operation there was increase of MCC to the values at start with the lowest level of circulation in the group older than 60.Conclusion. In older CHD patients the lowest level and lowest reserve of MCC were found compating to those younger than 60. At the background of artificial circulation there is lowering of peripheral MCC in both circulatory circles; once blood circulation has returned there is no complete restore of MCC because of low circulation in patients older than 60.